THE MODERN ECONOMIC THEORIES ON REDUCING THE UNEMPLOYMENT IN AN ECONOMY (Research Bulletins of the Faculty of Economic Sciences, 2021)
The controversies on the dependency between the inflation and the unemployment are one of the most famous macroeconomic relationship. The curve had been derieved from a statistical analysis carried out by A.W. Philips concerning the topic of dependen-cies between the unemployment and the nominal wages rates in Great Britain during the 1861-1957 period. The presented dependency has been widely criticised. One of the economical stream that had undertaken the criticism of the mentioned regularity of this relationship was the strand of the ”rational expectations”. This had brought a suprise to the economists. In the scope of schools and streams it could not match points of the paradigms. Nowadays it is included in the neoclasicism stream of the economics under the name of new classical economics, new classical macroekonomics or the school of the rational expectations. The content of the paper presents main areas of the criticism of the inflation and the unemployment dependance by Keynes's school. It shows actual relations of this area in a modern economy with the referance to selected European Union countries. We simultaneously seek for an answer on what was the basis of such a dynamic switch in the economical streams from the margin of neoclasicism to its main strand.
Keywords: inflation, unemployment, Philips’ curve, rational expectations